Faktor – Faktor yang Mempengaruhi Niat Investasi Cryptocurrency dengan Literasi Keuangan dan Literasi Keuangan Digital sebagai Variabel Moderasi - Delva Muharni; Rita Rahayu (Syntax Literate, 2023)
This research will discuss what factors influence the intention to use cryptocurrency as an investment option. In addition, this study also examines the moderating effect of financial literacy and digital financial literacy on factors that influence the intention to use cryptocurrency as an investment option. This research was conducted because cryptocurrency which is a form of technological development has been recognized as a commodity asset in Indonesia and has made people start to choose it as an investment option. Research on this topic needs to be continued in Indonesia because research on cryptocurrency digital currency is still rarely done in developing countries. Millennials and Generation Z in Indonesia are the population in this study because technological developments are widely accepted in these generations. The research data was obtained from a survey using a questionnaire which was then processed using SmartPLS 4.0. The results of this study prove that performance expectations, effort expectations, social influence and facilitating condition significantly influence intentions to use cryptocurrencies as an investment option. In addition, this study also found that there is no moderating effect of financial literacy and digital financial literacy on factors that influence the intention to use cryptocurrency as an investment option. Thus the Indonesian government needs to develop a strategy for the public regarding the benefits of cryptocurrency in order to increase the use of cryptocurrency as an alternative investment.